The Effectiveness of The Sufistic Core Character Learning Model in Increasing Student Religiosity and Character - H.M. Yahya, M. Wildan Bin; Rahmat, Munawar (International Journal Pedagogy of Social Studies, 2021)
The Qur'an-based Sufistic approach in religious education in Islamic boarding schools has proven to increase the students' holy obedience and noble character. But in college, this approach is never used. Religious education increases students ' religiosity and noble character with a conventional lecture approach (not a Sufistic approach). This study aims to test the effectiveness of the 'Sufistic Core Character' learning model to increase students' religiosity and morals. The research method used is quasi-experimental. The three experimental classes used the 'Sufistic Core Character' learning model, while the other three (control class) used the conventional learning model. The lecture material for both courses is the same, namely about religiosity and morality. Before the lecture, both types were tested (pre-test), and after eight lessons, they were tested again with the same test (post-test). As a result, there was an increase in scores in both classes studied. But the increase in scores in the experimental category was higher than in the control class. Thus, the 'Sufistic Core Character' learning model increases students' religiosity and noble character more effectively than conventional learning models.